Emerging Therapies in Nonexudative Age-Related Macular Degeneration in 2020. Issue 4 (July 2021) - Samanta, Anindya; Aziz, Aamir A.; Jhingan, Mahima; Singh, Sumit Randhir; Khanani, Arshad M.; Chhablani, Jay
Abstract : Abstract: Age-related macular degeneration (AMD) is one of the most common causes of severe vision loss in the developed world. Advanced forms of AMD are seen in primarily 2 types, exudative AMD involving the presence of choroidal neovascularization and nonexudative or dry AMD with geographic atrophy. For the latter, the combination of vitamins and minerals known as the Age-Related Eye Disease Study-2 formulation has been shown to decrease the rate of progression of nonexudative to exudative AMD, as no other treatments are currently approved for nonexudative AMD. This review will highlight upcoming treatments for nonexudative AMD. Six upcoming agents have shown results at least in the 2A phase. This includes intravitreal agents that are inhibitors of integrin (Risuteganib), intravitreal agents that disrupt the complement pathway (Zimura, APL-2), neuroprotective implants (Brimonidine DDS), a subcutaneous injectable (Elamipretide), and photobiomodulation (Valeda Light Delivery System).